2020
DOI: 10.1016/j.bbamcr.2020.118677
|View full text |Cite
|
Sign up to set email alerts
|

Role of S100 proteins in health and disease

Abstract: The S100 family of proteins contains 25 known members that share a high degree of sequence and structural similarity. However, only a limited number of family members have been characterized in depth, and the roles of other members are likely undervalued. Their importance should not be underestimated however, as S100 family members function to regulate a diverse array of cellular processes including proliferation, differentiation, inflammation, migration and/or invasion, apoptosis, Ca 2+ homeostasis, and energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
173
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(214 citation statements)
references
References 179 publications
1
173
0
2
Order By: Relevance
“…While some inhibitors seem to be effective by inhibiting the transcription of S100 genes, others inhibit S100 protein activity by disturbing the interaction between S100 proteins and their targets. In addition, targeting covalent modifications, such as S-nitrosylation, S-glutathionylation, and phosphorylation, could be a promising strategy, as these modifications influence the function of S100 proteins [213]. In this review, S100 inhibitors are classified into small molecule inhibitors, neutralising antibodies, and microRNA (miRNA) mimics, and a summary is given in Table 1.…”
Section: Targeting S100 Proteins For Cancer Therapymentioning
confidence: 99%
“…While some inhibitors seem to be effective by inhibiting the transcription of S100 genes, others inhibit S100 protein activity by disturbing the interaction between S100 proteins and their targets. In addition, targeting covalent modifications, such as S-nitrosylation, S-glutathionylation, and phosphorylation, could be a promising strategy, as these modifications influence the function of S100 proteins [213]. In this review, S100 inhibitors are classified into small molecule inhibitors, neutralising antibodies, and microRNA (miRNA) mimics, and a summary is given in Table 1.…”
Section: Targeting S100 Proteins For Cancer Therapymentioning
confidence: 99%
“…S100A6 is a Ca 2+ -binding protein belonging to the S100 family [1,2]. Members of this family are present in different cell and tissue types including the brain.…”
Section: Discussionmentioning
confidence: 99%
“…S100A6 is a low-molecular-weight Ca 2+ -binding protein of the S100 family [1,2]. It functions as a homodimer mainly formed by non-covalent interactions ( Figure 1) and binds two Ca 2+ per monomer, each through an EF-hand structure consisting of two α helices linked by a short loop region.…”
Section: Introductionmentioning
confidence: 99%
“…The S100 proteins were named because of their ability to dissolve in 100% neutral saturated ammonium sulfate solution and belong to a unique class of non-ubiquitous small molecular weight (10-12 kDa) (Bresnick et al, 2015), Ca 2+ -modulated proteins, which were first identified in nervous system by Moore (1965). The S100 family currently has 25 known different members (including S100A1-16, S100G, S100P, and S100B), which are highly similar in sequence and structure (Gonzalez et al, 2020), and they all contain calcium-binding protein motifs (Bresnick et al, 2015). Schafer and Heizmann (1996) reported that S100 proteins consist of two distinct helix-loop-helix elongation factor (EF) hands flanked by conserved hydrophobic regions at the C-and N-terminal and connected by a central hinge region.…”
Section: S100a8 and S100a9 Proteins: Important Members Of The S100 Prmentioning
confidence: 99%
“…There is growing experimental and clinical evidence that the S100 protein family has been implicated in the occurrence and development of multiple cardiovascular diseases, and these proteins are expected to become new targets for prevention (Gonzalez et al, 2020). For example, serum S100A levels increase after acute ischemic events, are highly sensitive in myocardial injury, and may be a candidate biomarker for the diagnosis of AMI (Aydin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%